2014
DOI: 10.1186/2050-6511-15-28
|View full text |Cite
|
Sign up to set email alerts
|

Diazoxide protects against doxorubicin-induced cardiotoxicity in the rat

Abstract: AimChemotherapy with doxorubicin is limited by cardiotoxicity. Free radical generation and mitochondrial dysfunction are thought to contribute to doxorubicin-induced cardiac failure. In this study we wanted to investigate if opening of mitochondrial KATP-channels by diazoxide is protective against doxorubicin cardiotoxicity, and if 5-hydroxydecanoate (5-HD), a selective mitochondrial KATP-channel antagonist, abolished any protection by this intervention.MethodsWistar rats were divided into 7 groups (n = 6) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Previous studies have shown that chemotherapy by DOX induces cardiovascular alterations by free radical generation and mitochondrial dysfunction, leading to ischemic or idiopathic dilated cardiomyopathy [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that chemotherapy by DOX induces cardiovascular alterations by free radical generation and mitochondrial dysfunction, leading to ischemic or idiopathic dilated cardiomyopathy [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically available agents such as losartan 72 , fluvastatin 73 , metformin 74 , iloprost 75 , and meloxicam 76 as well as other clinically unavailable ACEIs 69 71 have been shown to have cardioprotective results in vivo . Vasodilators 77 79 , neuropeptides 81 , and iron salts 80 have also been found to be useful. Finally, given that the pathogenesis of anthracyclines is in part related to increased oxidative stress 100 , several natural antioxidants (e.g.…”
Section: Cardioprotectantsmentioning
confidence: 99%
“…In addition to cytoprotective effects well documented in the literature, DZ was shown to represent a promising pharmacological intervention against cytotoxicity of the drugs known to cause severe impairment of mitochondria, such as isoproterenol and doxorubicin [8,66]. Moderation of ROS production ensuing from DZ administration [8,64,66] was shown to be a part of cytoprotective action.…”
Section: Nonspecific Cellular Targets Of Diazoxidementioning
confidence: 99%
“…Moderation of ROS production ensuing from DZ administration [8,64,66] was shown to be a part of cytoprotective action. However, no direct evidence for the involvement of mK ATP channel in cytoprotection was yet obtained in living organism.…”
Section: Nonspecific Cellular Targets Of Diazoxidementioning
confidence: 99%